Competitive ability of soybean cultivars with Ipomoea indivisa - Pazzini, Eduarda Posser; Galon, Leandro; Cavaletti, Daniel Cristian; Senhori, Victor Miguel; Henz Neto, Otilo Daniel; Müller, Caroline; Perin, Gismael Francisco (Revista de Ciências Agroveterinárias, 2022)
Among the weeds that infest soybeans, the morning glory (Ipomoea indivisa) stands out for competing with water, light, nutrients and also interfering in the crop harvesting process. The aim of this study was to test the competitive ability of soybean cultivars in the presence of I. indivisa, in substitutive experiments. The experiments were carried out in a completely randomized design, with four replicates, using the soybean cultivars M 5838, DM 53i54, DM 57i52, DM 66i68, NS 5445, and NS 6601. A constant final yield for soybean and I. indivisa was observed with 24 plants per pot. Relative and total productivities were analyzed using diagrams applied to substitutive experiments with soybean and I. indivisa plants proportions of 24:0, 18:6, 12:12, 6:18, and 0:24 plants pot-1 (crop:weed). On 35 days after the emergence of the culture and the I. indivisa, the morphophysiological characteristics of the plants were assessed and the relative competitiveness indices were calculated considering the 50:50 plant ratio (12:12 plants pot-1). Morning glory affected the morphophysiological characteristics of soybean cultivars, demonstrating superior competitive ability for environmental resources. There was a competition between soybean cultivars and I. indivisa, which caused reductions in the shoot dry matter for both species. In this study, interspecific competition was more harmful than intraspecific competition.